Effect of customised leaf colour chart (CLCC) based real time N management on agronomic attributes and protein content of rice (Oryza sativa L.) - Kumar, Prem Pal; Abraham, Thomas; Pattanaik, SSC; Kumar, Rakesh; Kumar, Upendra; Kumar, Anjani (ORYZA-An International Journal of Rice, 2018)
We conducted a field experiment at the Crop Research Farm, SHIATS, Allahabad (U.P.) during the kharif season of 2015 to evaluate the effect of customised leaf colour chart (CLCC) on yield and N content of rice. The experiment consisted of four level of nitrogen treatments 70, 80, 90 and 100% of recommended dose of nitrogen (RDN). Neem coated urea was applied based on CLCC and conventional method. The experiment was laid out in randomised block design with three replications. Significantly higher grain yield (5.93 t ha-1) and grain protein content (8.23%) were recorded under 100% RDN application based on CLCC. Real time N application based on CLCC, synchronised N supply and demand and hence partial factor productivity (PFPN ) was 11% higher as compared to 100% RDN application based onconventional method. Highest net income (Rs.47034 ha-1) and B:C ratio (1.90) were also recorded under 100% RDN application based on CLCC.